HIV prevention and HIV care among transgender and gender diverse youth: design and implementation of a multisite mixed-methods study protocol in the U.S. - Laura Jadwin-Cakmak; Sari L. Reisner; Jaclyn M. W. Hughto; Liz Salomon; Miguel Martinez; Elliot Popoff; Bré Anne Rivera; Gary W. Harper (BMC, 2019)
Abstract Background In the U.S., transgender and gender diverse (TGD) populations face structural, interpersonal, and individual barriers to healthcare. Less is known, however, about the HIV prevention and treatment experiences of TGD youth in the U.S. The current study was developed to fill this research gap. Methods This article describes the research protocol for a multi-site, U.S.-based mixed-methods study that sought to identify the multi-level facilitators and barriers that influence participation of TGD youth in various stages of the HIV prevention (e.g., pre-exposure prophylaxis uptake) and care continua. A sample of diverse TGD youth ages 16-24 was recruited from 14 U.S. sites. TGD youth participants completed a one-time, in-person visit that included an informed consent process, computer-based quantitative survey, and in-depth qualitative interview assessing experiences accessing HIV prevention and/or care services. Providers serving TGD youth were recruited from the same 14 sites and completed a one-time visit via phone that included informed consent, demographic questionnaire, and in-depth qualitative interview assessing their experiences providing HIV prevention or treatment services to TGD youth. Results Overall, 186 TGD youth ages 16-24 and 59 providers serving TGD youth were recruited and enrolled from across the 14 U.S. sites. TGD youth participants had a mean age of 20.69; 77.3% youth of color; 59.7% trans-feminine; 15.5% trans-masculine; 24.9% non-binary; 53.6% family income under poverty level. Providers included medical and mental health providers as well as case manager/care coordinators, HIV test counselors, and health educators/outreach workers. Providers were 81.3% cisgender and 30.5% people of color. Successes with community-engagement strategies and gender-affirming research methods are reported. Conclusions This study addresses critical gaps in current knowledge about the HIV prevention and care experiences of TGD youth. Findings have implications for the development of HIV interventions across levels to support the health and well-being of TGD youth. Future research is warranted to replicate and expand on lessons learned regarding recruitment and engagement of communities of TGD youth, including longitudinal designs to assess engagement across their developmental stages. Lessons learned working with TGD youth through developing and implementing the study protocol are shared. Trial registration Registered on ClinicalTrials.gov on 05/20/2015 (NCT02449629).